The boats of the "Glen Carrig" - Hodgson, William Hope, 1877-1918 (Floating Press, 2009)
The lifeboats of the sunken 'Glen Carrig' are lost in a strange sea. The survivors make landings on two strange islands, both of which seem to have been plucked from the drearier portions of Dante's Inferno. The sailors have to fight storms and monsters, but the main enemies seem to be the dismal islands themselves.